Effect of Chemical Stimulants on Chir Resin Yield - Prasad, Jayanti; Joshi, H. B. (Indian Forester, 1974)
Experiments to study the increase in resin yield through the application of chemical stimulants were undertaken during 1968 and 1969 by Silviculture Hill Division, U.P. at Ranikhet in consultation with F.R.I. From the treatments increases in resin yield from 26% to 33% have been achieved, in line with similiar results reported in F.R.I. experiments. The observations indicate that acid mixture of sulphuric and nitric acids in equal strengths of 20 to 25%, both in spray and kaolin paste positive results.